Continuation of underwater research at Trstenik in Kaštel Sućurac (In situ, 2025)
Since the ship Trstenik 3 was fully uncovered during the 2023 research campaign, this year's efforts are focused on detailed cleaning, removal of stringers, and the creation of comprehensive documentation regarding the condition of the ship's structure. The ship comprises the keel, the initial parts of the stem and the sternpost, six strakes on each side (comprising eleven planks on the north side and eight on the south). Each side also features a wale (the seventh strake). The structure includes thirty-four frames, consisting of floortimbers and half-frames as well as futtocks. Additionally, there are three stringers on the north side and two on the south, along with two short elements that appear to have served to support the stringers.
Keywords: Trstenik; Kaštel Sućurac; Roman economic complex; ship Trstenik 2; ship Trstenik 3